Heparan Sulfate–Rich Anionic Sites in the Human Glomerular Basement Membrane: Decreased Concentration in Congenital Nephrotic Syndrome - Vernier, Robert L; Klein, David J; Sisson, Susan P; Mahan, John D; Oegema, Theodore R; Brown, David M (The New England journal of medicine, 1983)
Recent work suggests that the normal barrier to penetration of the renal glomerular basement membrane by anionic plasma proteins may depend in part on the existence of negatively charged sites within the membrane. We describe an in vitro cytochemical method for the quantitative demonstration of anionic sites in the normal human glomerular basement membrane. In five normal subjects, ranging in age from 10 days to 57 years, the sites were distributed at regular intervals in the lamina rara externa, with a frequency of 23.8±6.8 sites per 1000-nm length of membrane. A similar distribution was observed in the basement membranes from three normal human fetuses. Ex vivo perfusion of one cadaver kidney revealed a similar distribution of anionic sites. The number of anionic sites in the glomerular basement membranes of five patients with the congenital nephrotic syndrome was reduced to 8.9±3.7 (P<0.001). Prior incubation of sections of normal kidney in purified heparinase resulted in a marked reduction in the number of anionic sites. We conclude that congenital nephrosis results from failure of heparan sulfate–rich anionic sites to develop in the lamina rara externa of the glomerular basement membrane. (N Engl J Med 1983; 309:1001–9.) EVIDENCE that the glomerular capillaries act as both a size and a charge barrier in the formation of the plasma ultrafiltrate 1 has accumulated during the past 10 years. Histochemical observations of kidneys from rats with proteinuria induced by the aminonucleoside of puromycin revealed a partial loss of the negative charges on the surface of glomerular epithelial cells from normal rats. 2 These sites were shown to consist of a sialic acid–rich glycoprotein coat. 2 Seiler et al. 3 subsequently demonstrated reversible losses of both these charged sites and the normal epithelial-cell foot-process structure after the perfusion of rat kidneys with cationic protamine sulfate, . . .